2019
DOI: 10.3390/molecules24173052
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Extraction Combined with In-Capillary [Fe(ferrozine)3]2+-CE-DAD to Screen Active Components with the Ability to Chelate Ferrous Ions from Flos Sophorae Immaturus (Flos Sophorae)

Abstract: An efficient microwave-assisted extraction (MAE) combined with in-capillary [Fe(ferrozine)3]2+-capillary electrophoresis-Diode Array Detector (in-capillary [Fe(ferrozine)3]2+-CE-DAD) was developed to screen active components with the ability to chelate ferrous ions and determine the total antioxidant activity. The MAE conditions, including methanol concentration, extraction power, extraction time, and the ratio of material to liquid, were optimized by an L9(34) orthogonal experiment. Background buffer, voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The migration and separation behaviour of the analytes are significantly affected by BGE [22]. At the initial stage of experiment, key factors of analysis including pH and concentrations of BGE, HP‐β‐CD, SDS, as well as content of ACN were progressively optimized by changing one factor for each time.…”
Section: Resultsmentioning
confidence: 99%
“…The migration and separation behaviour of the analytes are significantly affected by BGE [22]. At the initial stage of experiment, key factors of analysis including pH and concentrations of BGE, HP‐β‐CD, SDS, as well as content of ACN were progressively optimized by changing one factor for each time.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with traditional extraction methods, MAE reduces the consumption of time and solvent and increases the extraction yield; therefore, it is regarded as a green, efficient, and low‐cost extraction method (Bagade & Patil, 2021). MAE has been used to extract the antioxidant components of FSI, of which the main components were identified as rutin and quercetin (Liu et al., 2019). The extraction efficiency is affected by solvent type, particle size, microwave power, microwave time, and the liquid‐to‐solid ratio.…”
Section: Extraction Techniques For S Japonica Bioactive Compoundsmentioning
confidence: 99%
“…Flos sophorae immaturus ( FSI ) is the dried flower bud of Sophora japonic a L. This herb has a high flavonoid content and is considered a healthy food because of its high antioxidant activity ( Abdelhady et al, 2015 ; Li and Fan, 2020 ). FSI has been widely used for 2,000 years in China as an important traditional Chinese medicine, due to its antitumor, anti-inflammatory, and antibacterial activities ( Liu T. et al, 2019 ; Huang et al, 2020 ). Many studies have reported that the antioxidant compounds of FSI are responsible for its efficacy ( Yao et al, 2011 ; Zhang et al, 2011 ; Hu et al, 2016 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%